2017
DOI: 10.3847/1538-4357/aa80ea
|View full text |Cite
|
Sign up to set email alerts
|

The Post-periapsis Evolution of Galactic Center Source G1: The Second Case of a Resolved Tidal Interaction with a Supermassive Black Hole

Abstract: We present new adaptive optics (AO) imaging and spectroscopic measurements of Galactic center source G1 from W. M. Keck Observatory. Our goal is to understand its nature and relationship to G2, which is the first example of a spatially resolved object interacting with a supermassive black hole (SMBH). Both objects have been monitored with AO for the past decade (2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014) and are comparatively close to the black hole (a min ∼200-300 au) on very ec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(75 citation statements)
references
References 74 publications
(222 reference statements)
5
70
0
Order By: Relevance
“…Two general classifications of mechanisms are considered for the S-stars: (1) binary star systems scattered from outside the region and then tidally disrupted, leaving behind one component of the original binary while the other was ejected as a hypervelocity star (Hills 1988;Perets et al 2007); and (2) S-stars formed in the clockwise disk and then migrated to the central arcsecond around the SMBH (Levin 2007;Löckmann et al 2008;Merritt et al 2009). Previous works have also investigated how these S-stars relate to the clockwise disk, Wolf-Rayet stars, G2-like sources, and evolved giants in the region ; Bartko et al 2009;Do et al 2009Do et al , 2013Lu et al 2009;Phifer et al 2013;Chen & Amaro-Seoane 2014;Madigan et al 2014;Witzel et al 2014Witzel et al , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Two general classifications of mechanisms are considered for the S-stars: (1) binary star systems scattered from outside the region and then tidally disrupted, leaving behind one component of the original binary while the other was ejected as a hypervelocity star (Hills 1988;Perets et al 2007); and (2) S-stars formed in the clockwise disk and then migrated to the central arcsecond around the SMBH (Levin 2007;Löckmann et al 2008;Merritt et al 2009). Previous works have also investigated how these S-stars relate to the clockwise disk, Wolf-Rayet stars, G2-like sources, and evolved giants in the region ; Bartko et al 2009;Do et al 2009Do et al , 2013Lu et al 2009;Phifer et al 2013;Chen & Amaro-Seoane 2014;Madigan et al 2014;Witzel et al 2014Witzel et al , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…For each source, neighbouring Lʹ sources were subtracted out using the flux values identified with StarFinder. Kʹ-identified sources that were not associated with the Lʹ sources based on proper motions were also subtracted from the analysis image assuming that they had the same magnitude and colour profiles as our flux calibration sources (S0-2, S0-12, S1-20 and S1-1 9,17 ). The images were then background-subtracted and Lucy-Richardson deconvolved using the background map and model PSF generated from StarFinder.…”
Section: Extended Data Table 1 | Osiris Observations Used For the Orbmentioning
confidence: 99%
“…Several models (Methods section 'G-object formation scenarios') have been proposed to account for G2 in terms of an optically thick distribution of dust surrounding a star: a young, low-mass star (T Tauri star) that has retained a protoplanetary disk 25 or that generates a mass-loss envelope 26 , or the merger of a binary system 8,9,24,27 .…”
mentioning
confidence: 99%
“…For example, binaries are invoked to explain some long-standing observational puzzles, such as hypervelocity stars, the young stars in the S-cluster, the dark cusp, etc., (e.g., Hills 1988;Yu & Tremaine 2003;Antonini et al 2010;O'Leary et al 2009;Perets et al 2009;Alexander & Hopman 2009;Antonini & Perets 2012;Phifer et al 2013;Prodan et al 2015;Witzel et al 2014Witzel et al , 2017Stephan et al 2016). Furthermore, it has been suggested that compact object binaries in the GC are a potential source of gravitational wave emission (e.g., O'Leary et al 2009;Antonini & Perets 2012;Prodan et al 2015;Hoang et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In such a system, gravitational perturbations from the SMBH can induce large eccentricities on the binary orbit, which can cause the binary members to merge (see for review of the dynamics Naoz 2016). This coalescence may form a new star that can look like the G2 and G1 objects (Phifer et al 2013;Prodan et al 2015;Witzel et al 2014Witzel et al , 2017Stephan et al 2016), which may eventually become blue stragglers (e.g., Naoz & Fabrycky 2014).…”
Section: Introductionmentioning
confidence: 99%